Effect of feed and holding conditions on survival and growth of juvenile crayfish Pontastacus leptodactylus and Faxonius limosus - Kropielnicka-Kruk Katarzyna; Ulikowski Dariusz; Wasilewska Agnieszka (Fisheries & Aquatic Life)
In the European natural environment attempts are undertaken to replace invasive crayfish species with native ones. For this purpose, aquaculture of crayfish is required, but their behaviour and the lack of balanced feeds impede further development. To effectively eliminate invasive crayfish, more knowledge is needed, in context of their similarities and differences from native species. This study investigates two crayfish species, native Pontastacus leptodactylus and invasive Faxonius limosus in relation to different holding conditions and feeds. Juvenile crayfish were exposed to two types of holding conditions, inside (IN) in tap water and outside (OUT) in water with natural plankton content. In addition, three feeds were tested, sinking chips (F1), flakes (F2) and floating sticks (F3). The feeds composition was similar, but sinking times differed and were quick for F1 and slow for F2 and F3, which provided extended visual and chemical exposure to crayfish. The significant effect of holding conditions on survival was found for both species, with highest results for OUT holding conditions, suggesting important role of natural plankton in survival. Three feeds (F1, F2 and F3), showed no effect for P. leptodactylus but F2 and F3 improved growth in F. limosus, indicating more efficient utilisation of the detected feed.